1984
DOI: 10.1017/s0022112084001026
|View full text |Cite
|
Sign up to set email alerts
|

Study of turbulent structure with hot wires smaller than the viscous length

Abstract: The small-scale structure of the streamwise velocity fluctuations in the wall region of a turbulent boundary layer is examined in a new wind-tunnel facility using hot-wires smaller than any previously constructed (typical dimensions: l = 25 μm, d = 0.5 μm). In the boundary layer in which the measurements were made, the ratio of the hot-wire length to the viscous length is 0.3. The turbulent intensity measured with the small hot wires is larger than that measured with longer wires owing to the better spatial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 14 publications
5
40
0
Order By: Relevance
“…The present data are 6% higher than Johansson and Alfredsson's RMS values at y + = 10.3 and y + = 15.8. This is consistent with the data of Willmarth and Sharma (1984) who showed that a hot wire with an l + = 14 should yield RMS levels approximately 8% lower than the true RMS value a t y + = 13.3.No evidence of mean velocity broadening were seen in any of the RMS results due to the size of the probe volume normal to the wall. This was expected since the broadening correction scheme of Karpuk and Tiederman (1976) predicts corrected values of u' less than 0.3% different than the uncorrected value in the worst case for the present measurements.…”
supporting
confidence: 90%
“…The present data are 6% higher than Johansson and Alfredsson's RMS values at y + = 10.3 and y + = 15.8. This is consistent with the data of Willmarth and Sharma (1984) who showed that a hot wire with an l + = 14 should yield RMS levels approximately 8% lower than the true RMS value a t y + = 13.3.No evidence of mean velocity broadening were seen in any of the RMS results due to the size of the probe volume normal to the wall. This was expected since the broadening correction scheme of Karpuk and Tiederman (1976) predicts corrected values of u' less than 0.3% different than the uncorrected value in the worst case for the present measurements.…”
supporting
confidence: 90%
“…In order to minimize these errors a very small x-wire is needed or, alternately, measurements in a thick boundary layer must be made. Examples of these two approaches are give by the studies of Willmarth and Sharma (1984), who used small x-wires, and by Eckelmann…”
Section: Resolution Errorsmentioning
confidence: 99%
“…They investigated wall pressure fluctuations in conjunction with the mean velocity profiles. Willmarth and Sharma (1984) and Snarski and Lueptow (1995), performed similar studies where also the turbulent flow properties were investigated. In the latter study two different groups of fluctuations in the turbulent boundary layer surrounding a cylinder were identified.…”
Section: Literature and Fluid Mechanical Backgroundmentioning
confidence: 99%
“…All these works investigate wall pressure fluctuations in conjunction with the mean velocity profiles. In Willmarth and Sharma (1984) and later also in Snarski and Lueptow (1995), similar studies were performed where the turbulent flow properties also were investigated. However, despite decades of research on the subject, there is still uncertainty over many of the fundamental relations for turbulent, axisymmetric boundary layers.…”
Section: Previous Workmentioning
confidence: 99%